2005
DOI: 10.1103/physrevb.72.165203
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic and electronic transport percolation in epitaxialGe1xMnxfilms

Abstract: Electronic transport and magnetic properties of Ge 1-x Mn x /Ge(100) films are investigated as a function of Mn dilution. Depending on x, characteristic temperatures separate different regimes in both properties. Resistivity exhibits an insulator-like behavior in the whole temperature range and, below about 80 K, two distinct activation energies are observed. At a higher temperature value, T R , resistivity experiences a sudden reduction. Hall coefficient shows a strong contribution from the anomalous Hall eff… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
69
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(77 citation statements)
references
References 23 publications
5
69
0
Order By: Relevance
“…Below T B , nonzero magnetisation in the absence of an external field, as well as hysteresis in magnetisation loops is observed, which is due to a blocking process of the superparamagnetic precipitates. Therefore our study indicates that reports on hysteresis in magnetisation loops 7,8 and a field induced magnetisation onset near room temperature 4 in possibly diluted magnetic semiconductors might be a result of the presence of precipitates in the films. At low temperatures, samples with 70 • C ≤ T S < 120 • C undergo a transition into a metastable state that is interpreted as a signature of an inhomogeneous Mn dispersion in the Ge matrix observed in addition to the precipitates.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Below T B , nonzero magnetisation in the absence of an external field, as well as hysteresis in magnetisation loops is observed, which is due to a blocking process of the superparamagnetic precipitates. Therefore our study indicates that reports on hysteresis in magnetisation loops 7,8 and a field induced magnetisation onset near room temperature 4 in possibly diluted magnetic semiconductors might be a result of the presence of precipitates in the films. At low temperatures, samples with 70 • C ≤ T S < 120 • C undergo a transition into a metastable state that is interpreted as a signature of an inhomogeneous Mn dispersion in the Ge matrix observed in addition to the precipitates.…”
Section: Discussionmentioning
confidence: 96%
“…Various fabrication techniques have recently been employed to realise GeMn magnetic semiconductors, including single crystal growth, 1 solid phase epitaxy 2 and molecular beam epitaxy (MBE). 3,4,5,6,7,8,9 Irrespective of the fabrication technique, the formation of ferromagnetic, intermetallic compounds can occur. Bulk thin intermetallic films have been observed on Ge(111), 2 while phase separation was found on a µm scale in single crystals 1 and on a sub-µm scale in MBE fabricated samples.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the hole mediated effect discovered in Mn x Ge 1-x DMS opens up tremendous possibilities to realize spintronic devices with advantages in reducing power dissipation and increasing new functionalities, leading to perhaps normally off computers. To date, there are many reports on the Mn x Ge 1-x growth and characterizations by molecular beam epitaxy (MBE) (Park et al, 2002, Li et al, 2005, Jamet et al, 2006, Tsui et al, 2003, Ahlers et al, 2006a, Ahlers et al, 2006b, Bougeard et al, 2006, Devillers et al, 2007, Li et al, 2007, Park et al, 2001, Wang et al, 2008a, Pinto et al, 2005b, ion implantation (Park et al, 2005, Lin et al, 2008, Verna et al, 2006, D'Orazio et al, 2002, Liu et al, 2004, Lifeng et al, 2004, and bulk crystal growth (Cho et al, 2002, Biegger et al, 2007. We can divide them here, for an easier orientation, into two groups: those that cover fundermantal studies of phase formation, ferromagnetism, and transport properties (Park et al, 2002, Li et al, 2005, Majumdar et al, 2009a, Wang et al, 2008a, Gunnella et al, 2005, Liu et al, 2006, Jamet et al, 2006, Li et al, 2006b, Zhu et al, 2004, Miyoshi et al, 1999, Li et al, 2006a, Zeng et al, 2006, Cho et al, 2002, Liu and Reinke, 2008, Gambardella et al, 2007…”
Section: Overview Of the Mn Doped Gementioning
confidence: 99%
“…Since then, various preparation techniques were employed in order to produce Mn-doped Ge DMS, including aforementioned MBE (Li et al, 2005, Jamet et al, 2006, Tsui et al, 2003, Ahlers et al, 2006a, Ahlers et al, 2006b, Bougeard et al, 2006, Devillers et al, 2007, Li et al, 2007, Park et al, 2001, Wang et al, 2008a, Pinto et al, 2005b, single-crystal growth (Cho et al, 2002, Biegger et al, 2007, and ion implantation (Park et al, 2005, Lin et al, 2008, Verna et al, 2006, D'Orazio et al, 2002, Liu et al, 2004, Lifeng et al, 2004, aiming to further increase T c and to obtain the electric field controllability at room temperature (Biegger et al, 2007). Among these efforts, Cho et al (Cho et al, 2002) reported the synthesis of Mn doped bulk Ge single crystals with 6 % of Mn and a high ferromagnetic order at about 285 K via a vertical gradient solidification method.…”
Section: Overview Of the Mn Doped Gementioning
confidence: 99%
“…The most commonly used n-type dopants are sulphur, selenium, tellurium, tin, silicon, carbon, germanium and p-type dopants are zinc, beryllium, magnesium, cadmium, silicon, carbon, germanium. Si, C and Ge act as both n and p-type dopants that are capable of replacing the Ga or As atom in the crystalline structure [15]. Figure 1 shows relationship between Lattice Constants, Band gap energies and Band-gap wavelength of II-VI compounds [16].…”
Section: Growth Techniquesmentioning
confidence: 99%